Personal Archives of Teachers and History of Mathematics Teaching Professional Knowledge - Wagner Rodrigues Valente (Educação & Realidade, 2021)
This article aims to emphasise the importance of the personal archives of mathematics teachers for the analysis of the dynamics and processes for the elaboration of teaching professional knowledge. For this, it uses the concept of scientific field that comes from the studies of Pierre Bourdieu. It also takes as theoretical references the work of researchers Rita Hofstetter and Bernard Schneuwly, who address the construction of reference knowledge for teaching and, also, the studies of Peter Burke on the history of knowledge. By historically analysing the trajectory of discussions about mathematics in teacher education, the study concludes that the documentation contained in personal collections of mathematics teachers enables the analysis of the clashes that have occurred over time between disciplinary fields and the professional field of teaching, in terms of the production of the professional knowledge of the mathematics teacher.